2022
DOI: 10.1021/acsnano.2c05130
|View full text |Cite
|
Sign up to set email alerts
|

Optically Detected Magnetic Resonance Spectroscopy of Cu-Doped CdSe/CdS and CuInS2 Colloidal Quantum Dots

Abstract: Copper-doped II−VI and copper-based I−III−VI 2 colloidal quantum dots (CQDs) have been at the forefront of interest in nanocrystals over the past decade, attributable to their optically activated copper states. However, the related recombination mechanisms are still unclear. The current work elaborates on recombination processes in such materials by following the spin properties of copper-doped CdSe/CdS (Cu@CdSe/CdS) and of CuInS 2 and CuInS 2 /(CdS, ZnS) core/shell CQDs using continuous-wave and time-resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…As discussed above, the strong hole localization quenches the orbital magnetic moment and the hole state becomes a pure-spin state. Indeed, recent optically detected magnetic resonance studies on CuInS 2 QDs showed that g e ≈ g h . Thus, the observed insensitivity of the PL lifetimes to magnetic field is indeed expected for the free-to-bound PL mechanism.…”
Section: Results and Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…As discussed above, the strong hole localization quenches the orbital magnetic moment and the hole state becomes a pure-spin state. Indeed, recent optically detected magnetic resonance studies on CuInS 2 QDs showed that g e ≈ g h . Thus, the observed insensitivity of the PL lifetimes to magnetic field is indeed expected for the free-to-bound PL mechanism.…”
Section: Results and Discussionmentioning
confidence: 70%
“…Indeed, recent optically detected magnetic resonance studies on CuInS 2 QDs showed that g e ≈ g h . 62 Thus, the observed insensitivity of the PL lifetimes to magnetic field is indeed expected for the free-tobound PL mechanism.…”
Section: Magnetic Field Dependence Of Photoluminescence Dynamicsmentioning
confidence: 78%
“…S6 †). 67,68 These small molecules represent the experimentally used long-alkyl-chain passivating ligands. 17,21 The geometry optimization of these ligand-passivated QDs exhibits minimal modifications on the surface structure compared to their bare counterparts (ESI, section S4 and Table S1 †).…”
Section: Static Structural Propertiesmentioning
confidence: 99%
“…29,30 Radiative recombination of delocalized conduction band electrons and localized holes at the Cu site gives rise to distinct photoluminescence (PL) bands and long excited state lifetimes. [31][32][33][34] These chemically modi-fied QDs also provide functional advantages such as reduced reabsorption, efficient light conversion, and tunability, proposing their unique applications. [35][36][37] The creation of localized defect states indicates well-defined and indistinguishable photon emission.…”
Section: Introductionmentioning
confidence: 99%
“…[7] For example, Fuhr et al [3] developed the Cu 1 + /Cu 2 + -defect model, and showed that band-edge optical properties are strongly influenced by the native optically active defects. Harchol et al [8] recently explored the luminescence mechanism, further indicating that this model also involves recombination of a self-trapped exciton localized around the copper site. Meanwhile, multi-state relaxation pathway, [9] and donor-acceptor pair emission [10] have also been proposed.…”
Section: Introductionmentioning
confidence: 99%